(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
Identification is the determination of the individuality of a person based on certain physical characteristics1. Question of identification in living persons arises in criminal cases such as in those accused of assault, murder, rape etc., in interchange of newborn babies in the hospital and in impersonation. In civil cases like marriage, inheritance, insurance claims, disputed sex etc. identification plays an important role2. when establishing the identity of an individual, primary characteristics of identification are sex, age, and stature1. One of the cardinal parameters for identification is determination of sex. Sex determination of unidentified skeletal remains from crime scenes or excavation sites is an important component for identification in forensic anthropology. Determination of sex from the human skeleton is among the most important aspect of establishing the biological profile of unknown individuals. In case of mass-disasters such as armed conflicts, terrorist massacres, airplane crashes, war related crimes etc. when badly decomposed, mutilated or damaged human remains consisting of only a few bones or their fragments are recovered from the site; in such cases, it becomes crucial to establish the biological identity, especially the sex of a missing individual because of differences in the age of epiphyseal fusion and difference in formulae for stature estimation in both sexes3. Accurate sex determination thus, provides valuable evidences to a forensic scientist with regard to identification of remains. Of the human skeleton, the humerus often remains in good condition and is especially favorable for metric sex determination4.